Pengaruh Kenaikan Harga Telur Terhadap Daya Beli Masyarakat Di Tangerang - Hendriyati Haryani; Annisa Widya F; Nita Septiani (UNIVERSITAS RAHARJA, 2023)
This study aims to determine the increase in the price of chicken eggs in Tangerang City. The research was conducted from September to November 2022. The research method is a survey method. The data collection method used in this study is a non-probabilistic technique using simple random sampling and snowballing sampling. The data analysis method used is a quantitative method with multiple linear regression analysis models. From the results of the study that the results of the analysis of the increase in the price of chicken eggs affect the demand for the price of chicken eggs in Tangerang City. There is a significant effect on the price of chicken eggs, the price of other goods, and income simultaneously on the increase in the price of chicken eggs in Tangerang City, and there is a significant effect on the price of chicken eggs and income partially on the demand for chicken eggs in Tangerang City, then there is no significant effect on the price of goods others (chicken meat) partially to the demand for chicken eggs in Tangerang City.